THE DEFINITION OF THE OPTIMAL AREAS OF INPUT OF SOLID ADDITIVES INTO THE AIR INLET OF THE BOILER - O. S. Dmitrieva; S. F. Loraj; V. Je. Zinurov; Je. R. Zvereva; M. F. Shageev (Известия высших учебных заведений: Проблемы энергетики)
The conditions of operation of the main and auxiliary equipment of TPPs essentially depend on the quality of fuel oil. The article considers the problem of improving the combustion process of fuel oil and associate produced by burning of sulfur oxides due to the introduction of additives. A part of the duct of the boiler is simulated up to the burners, where the additive particles are introduced. Areas of entrainment of particles in the duct of the boiler are investigated for uniform addition of the additive.